2010
DOI: 10.1111/j.1741-2358.2009.00298.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of resin‐bonded extracoronal attachments with removable partial denture: case report

Abstract: Dentures with resin-bonded extracoronal attachments can have a number of advantages over traditional clasp-retained removable partial dentures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
0
4
0
1
Order By: Relevance
“…So, the goal of this study was to assess the strains transferred by zirconia and metal RBAs to the distal extension RPD supporting structures, as well as to compare them with those created by extracoronal attachment with complete veneer retainers. 5,11,15 This study was conducted in-vitro in order to have more control over the variables and to allow for better assessment of the changes that occurred. It has been proven that in-vitro studies are more frequently used in the stress analysis of oral structures than invivo research because the histological structures of periodontal tissues and bone consistency differ between patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…So, the goal of this study was to assess the strains transferred by zirconia and metal RBAs to the distal extension RPD supporting structures, as well as to compare them with those created by extracoronal attachment with complete veneer retainers. 5,11,15 This study was conducted in-vitro in order to have more control over the variables and to allow for better assessment of the changes that occurred. It has been proven that in-vitro studies are more frequently used in the stress analysis of oral structures than invivo research because the histological structures of periodontal tissues and bone consistency differ between patients.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] Several authors have reported on the use of metal-bonded components as rest seats, guide plates, attachments and retention undercuts. [12][13][14][15][16] Marinello and Scharer 1991 7 treated 34 patients with RBAretained RPDs. In which etched metal castings with extracoronal attachments had been in service for 28 months.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8] Extracoronal adhesive attachments 9 made from metal alloys have been advocated. [10][11][12] However, sufficient bonding area, discoloration of abutment teeth, and space requirements in the vertical dimension are limitations which lead to unfavorable survival rates. 13,14 Substantial advances in adhesive dentistry, 15-17 positive experience with zirconia ceramic 18-21 as a restorative material, and the current status of intraoral scanning and computer-aided design and computer-aided manufacturing (CAD-CAM) 22,23 might revive the minimally invasive concept of adhesive attachments as a cost-effective treatment option.…”
mentioning
confidence: 99%
“…Este tipo de tratamento apresenta uma série de vantagens como mínima redução dental, margens supragengivais, favorável distribuição de stress e ótima estética. Orsi et al (2009) reportaram um caso clínico de reabilitação oral usando a combinação de attachment extracoronário adesivo com barra de Dolder e prótese parcial removível, e concluíram que próteses com attachments adesivos extracoronários têm certas vantagens em relação às próteses parciais removíveis convencionais com grampos: estética, retenção e eficiência mastigatória.…”
Section: Encaixes Extracoronáriosunclassified